Excitation of gravity modes in the parameter space of the tidal wind system - Blanco, S. (2000)
Perturbing the Navier-Stokes equation in the ionospheric F-region, the dispersion relation and the unstable regions in wavenumber space are derived as a function of two control parameters, the colatitude θ and the slow time evolution for tidal modes τ. Our results satisfy the internal gravity wave (IGW) dispersion relation and are in good agreement with observational data. Also, we obtained a nice prediction for the excitation regions of these modes in the parameter space (θ, τ). The distribution of IGW excitations, in this parameter space is in very good agreement with observational data distributed along the day. An alternative explanation to the disappearence of IGW near the equator is given. Our model predicts an interesting latitude dependence, which needs to be tested by new observational data.